Czech Students’ Perceptions of Ethical Behavior in Business and Entrepreneurship - Dennis Barber III; John H. Batchelor; Timothy Hatten; Shanan G. Gibson; Ladislav Rolínek (Business Ethics and Leadership)
The central notion of business culture and communication with stakeholders consists in the ethical standards regarding the behaviour of corporation owners and managers, which, on the one hand, form an essential element of successful business activities and partnerships, and on the other hand, are complicated in terms of measuring and managing the phenomenon. This study uses agency and stakeholder theories to compare the ethical standards in the behaviour of businessmen and managers. These theories influence freedom of decision-making and behaviour in entrepreneurial activity based on the personal ethical considerations and individuals’ interests, regardless of the size of their share in the business. The article analyzes data regarding differences in perceptions of business owners and managers by Czech students; the differences between ethical standards of behaviour of Czech and American entrepreneurs and managers; gender peculiarities of Czech students’ perception of different business representatives. A methodological tool for the study of ethical perception by youth at the University of the Czech Republic was the Bucar and Hisrich model, and the basis to define the statistical significance of testing the hypothesis ̶ even and odd T-tests. The object of the study contains representatives of small and medium-sized businesses in the Czech Republic, as a country that offers an appealing microcosm for research thanks to the recent transition to a market economy with rapid changes in policy and market activity perceptions. 73% of respondents previously worked in a small business, almost 44% had family members who owned or have a small business and 9.5% owned the business. The sample age structure consisted of 53% of women and 47% of men, on average, under 22 years old, 8% of whom were married. The results of the research revealed that there were no significant differences between the Czech students’ ethical perception of managers and businessmen and the lack of influence on the respondents’ previous experience in doing business. A study of gender-based sampling revealed that Czech female students are more likely to evaluate entrepreneurs less ethically than men do.